Carbon capture : sequestration and storage - Hester, R. E. (Royal Society of Chemistry, 2009)
Reports on methods of capturing and storing CO2 from major sources to reduce the levels emitted to the atmosphere by human activities. Carbon Capture and Storage (CCS) is the only method available for reducing CO2 emissions while allowing continued use of fossil fuels, both for power generation and potentially in broader contexts. Carbon capture technologies are already playing a role in reducing emissions from large sources such as power stations. Carbon capture could potentially tackle these emissions, either by use of photosynthetic organisms to fix carbon, providing a biomass energy source or by direct capture from the air. Various potential options are available for carbon storage, including geological, mineral and ocean storage. This book describes the current options available and discusses the potential for future CCS strategies.
Keywords: Carbon sequestration.; elektronické knihy; electronic books